Progesterone Administration Modulates Cortical TLR4/NF-κB Signaling Pathway after Subarachnoid Hemorrhage in Male Rats - Zhong Wang; Gang Zuo; Xiao-Yong Shi; Jian Zhang; Qi Fang; Gang Chen (Mediators of Inflammation)
Our previous study concerning brain trauma has shown that progesterone could regulate toll-like receptor 4 (TLR4) and nuclear factor-kappa B (NF-κB) signaling pathway in the brain, which also has been proved to play important roles in early brain injury (EBI) after subarachnoid hemorrhage (SAH). The aim of the current study was to investigate whether progesterone administration modulated TLR4/NF-κB pathway signaling pathway in the brain at the early stage of SAH. All SAH animals were subjected to injection of 0.3 ml fresh arterial, non-heparinized blood into prechiasmatic cistern in 20 seconds. Male rats were given 0 or 16 mg/kg injections of progesterone at post-SAH hours 1, 6, and 24. Brain samples were extracted at 48 h after SAH. As a result, SAH could induce a strong up-regulation of TLR4, NF-κB, pro-inflammatory cytokines, MCP-1, and ICAM-1 in the cortex. Administration of progesterone following SAH could down-regulate the cortical levels of these agents related to TLR4/NF-κB signaling pathway. Post-SAH progesterone treatment significantly ameliorated the EBI, such as the clinical behavior scale, brain edema, and blood-brain barrier (BBB) impairment. It was concluded that post-SAH progesterone administration may attenuate TLR4/NF-κB signaling pathway in the rat brain following SAH.